Penyelesaian Sengketa Tanah Terkait Kepemilikan Hak Atas Tanah(Studi Kasus Putusan Pengadilan Negeri SurakartaNo.87/Pdt.G/2011/PN.Ska) - Cahyono, Tri; , Shallman Al Farizi, S.H., M.Kn (2016)
There is a land dispute at Jalan Brig Sudiarto No. 68 Ex. Joyosuran district. POND market, Surakarta, where plaintiff resolve through the courts. This study aims to determine the settlement of land disputes between citizens and residents and to determine the legal consequences of the decisions that have been there. The research method using normative methods for the research carried out on Surakarta District Court No.87/Pdt.G/2011/PN.Ska. Collecting data using secondary data, especially the decision No. 87/Pdt.G/2011/PN.Ska and use the scientific literature. The data analysis is done by using deductive thinking framework to address the problem. Legal considerations judges already have permanent legal force, and the decision is in conformity with the regulations in force today.